2012
DOI: 10.1039/c2jm15674a
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction with organic thin layer for three dimensional high performance hybrid solar cells

Abstract: Hybrid solar cells based on composites of silicon nanopillar arrays (SiNPs) on silicon substrates and conjugated polymer were investigated in this study. SiNPs with three dimensional (3D) geometry could orthogonalize the directions of light absorption and charge transfer while allowing for enhanced light scattering and trapping. In addition, SiNPs were fabricated by a simple process at low temperature and displayed strong light trapping capability over a wide range of incidence angles as well as near infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 37 publications
4
44
0
Order By: Relevance
“…In earlier reports, it has been shown that organic and inorganic hybrid combination has complementary advantages, such as high carrier mobility and wide absorption spectrum from the inorganic side, and low temperature solution processability and low cost processability from the organic side [4,5]. Till now, most organic-inorganic hybrid structured devices were demonstrated on rigid substrates [6][7][8][9], since most inorganic materials typically need a rigid platform for their deposition or growth [1].…”
Section: Introductionmentioning
confidence: 98%
“…In earlier reports, it has been shown that organic and inorganic hybrid combination has complementary advantages, such as high carrier mobility and wide absorption spectrum from the inorganic side, and low temperature solution processability and low cost processability from the organic side [4,5]. Till now, most organic-inorganic hybrid structured devices were demonstrated on rigid substrates [6][7][8][9], since most inorganic materials typically need a rigid platform for their deposition or growth [1].…”
Section: Introductionmentioning
confidence: 98%
“…Several kinds of organic materials, including conjugated polymers [1][2][3][4]8], conjugated small molecules [9,10], and fullerene derivatives [11], are used as hole or electron transporting layer in hybrid solar cells. Among them, poly (3,4-ethylenedioxythiophene): polystyrene (PED-OT:PSS), a conducting polymer widely used as a hole transporting layer or metal-free electrode in organic electronic devices, has been proven to be commendable to act as a hole transporting layer in hybrid solar cells [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…c) Dopamine detection on pc12 cells under hypoxic stimulation. [288] Copyright 2017, RSC. The real-time measurements show signal change when hypoxia is generated, and a comparison for different oxygen concentrations, including absence of signal change when Ca 2+ channels are blocked with cadmium ions.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%